DESKRIPSI PENERAPAN PEMBELAJARAN TEMATIK MODEL E-LEARNING BERBASIS GOOGLE CLASSROOM KELAS IV DI SDIT AL MUMTAZ PONTIANAK KOTA - Nur Cantika; Suparjan Suparjan; Rio Pranata (Universitas Tanjungpura, 2021)
AbstractThis research generally aims to describe the application of thematic learning model of elearning based on google classroom class IV at SDIT Al-Mumtaz Pontianak City. This research uses qualitative research with descriptive method. Participants in this study acted as data informants consisting of grade IV A, IV B, IV C and IV D teachers and the source of the data in this study was obtained from the application of the thematic learning model of e-learning based on google classroom. The research instrument is the human instrument, namely the researcher. The data collection techniques used were interviews, observation, and documentation studies. The data analysis technique used is the Miles and Huberman model which includes four stages, namely data collection, data reduction, data presentation, and drawing conclusions. The results of the study indicate that teachers have planned by preparing Learning Instruments, namely Learning Implementation Plans (RPP), media and materials, and communicating between teachers and parents or students, namely regarding the availability of devices/laptops/computers and internet access, online learning applications, how to the use of online applications, online learning materials and schedules, supports the online learning process. Then the implementation is generally carried out such as interacting in learning, providing feedback, instructing students to study independently, using various Information and Communication Technology-based learning resources, and conducting assessment activities. Furthermore, the content in the learning is in the form of powerpoints which are used as pdfs and learning video links. Then the assessment in google classroombased learning is the cognitive (knowledge) and psychomotor (skills) domains. Assessment of the affective domain (attitude) cannot be done in google classroom-based learning.Keywords: Description, Thematic Learning, E-learning, Google Classroom.